Title Effect of Deuteron Structure on Hyperfine Splitting of Deuterium - Azam, Sikandar (My University, 1987)
The hyperfine splitting (hfs) of deuterium shows a substantial deviation from the prediction based on Fermi's formula. This reflects the effect of the deuteron structure which was not taken account of in Fermi's formula. Following Bohr's original work on the deuteron structure effect, several calculations were done prior to the 1960's, using nucleon-nucleon (NN) potentials which are from today's standard, rather primitive. In this thesis we reexamine this problem by using several modern realistic NN potentials which reproduce the deuteron properties and the NN scattering data very well. In addition to the correction of the type which was examined by Bohr and Low, we examine a number of other corrections. The Bohr-Low correction, which is the most important one, turns out to be remarkably insensitive to the choice of the potential, and this correction significantly over-estimates the experimentally observed anomaly. However, the correction arising through the angular momentum dependent terms in the NN potential is sensitive to the choice of the potential. When this effect is included the theory and experiment can be reconciled for some of the potentials. In this sense the long standing anomaly of the deuterium hfs can be explained.
Keywords: Physical Sciences and Mathematics; Physics; Physical Sciences and Mathematics